Influence of Metabolic Parameters and Treatment Method on OCT Angiography Results in Children with Type 1 Diabetes. (18th November 2020) - Wysocka-Mincewicz, Marta; Baszyńska-Wilk, Marta; Gołębiewska, Joanna; Olechowski, Andrzej; Byczyńska, Aleksandra; Hautz, Wojciech; Szalecki, Mieczysław
Abstract : Aim . To evaluate the influence of metabolic parameters and the treatment method in children with type 1 diabetes (T1D) on the optical coherence tomography angiography (OCTA) results as early markers of diabetic retinopathy (DR). Material and Methods . This prospective study enrolled 175 consecutive children with T1D. OCTA was performed using AngioVue (Avanti, Optovue). Whole superficial capillary vessel density (wsVD), fovea superficial vessel density (fsVD), parafovea superficial vessel density (psVD), whole deep vessel density (wdVD), fovea deep vessel density (fdVD), parafovea deep vessel density (pdVD), foveal thickness (FT), parafoveal thickness (PFT), and foveal avascular zone (FAZ) in superficial plexus were evaluated and analyzed in relation to individual characteristics, i.e., sex, weight, height, body mass index (BMI), and metabolic factors: current and mean value of glycated hemoglobin A1c (HbA1c). Furthermore, the analysis concerned the diabetes duration, age at the T1D onset, and type of treatment—multiple daily insulin injections (MDI) or continuous subcutaneous insulin infusion (CSII). Results . In the study group, we did not identify any patient with DR in fundus ophthalmoscopy. Age at the onset of diabetes correlated negatively with FAZ (r = − 0.17, p < 0.05 ). The higher level of HbA1c corresponded to a decrease of wsVD (r = − 0.13, p < 0.05 ). We found significantly lower fsVD (32.25 ± .1 vs. 33.98 ± .1, p < 0.01 ), wdVD (57.87 ± .1 vs. 58.64 ± .9, p < 0.01 ), and pdVD (60.60 ± .2 vs. 61.49 ± .1, p < 0.01 ) and larger FAZ area (0.25 ± .1 vs. 0.23 ± .1, p < 0.05 ) in the CSII vs. MDI group. Conclusion . The metabolic parameters, age of the onset of diabetes, and treatment method affected the OCTA results in children with T1D. Further studies and observation of these young patients are needed to determine if these findings are important for early detection of DR or predictive of future DR severity.